Augmented Lagrangian method for optimal control of interconnected systems - Leong, Wah June; Yap, Hong Keat; Sim, Hong Seng (Penerbit Universiti Malaysia Perlis, 2024)
This paper explores the application of the augmented Lagrangian method (ALM) for constructing optimal control of some interconnected systems. The ALM proves to be a robust technique in handling the stability and observability restrictions arising from interconnections among subsystems. By segregating Lagrange multipliers from the solution process, the method effectively solves the optimal control problems in a simpler unconstrained setting. The proposed approach is substantiated through numerical simulation, demonstrating its efficacy in obtaining optimal control strategy for the interconnected networks of a power grid model.